Massive open online courses (MOOCs) as a window into the veterinary profession. (18th February 2017) - Paterson, J.; Hughes, K.; Steer, L.; Das Gupta, M.; Boyd, S.; Bell, C.; Rhind, S.
Abstract : Massive open online courses (MOOCs) are freely available online courses open to anyone who registers and typically are associated with thousands or hundreds of thousands of participants. Using an established online platform, the authors created and delivered a five‐week MOOC aimed primarily at prospective veterinary students, but open to anyone with an interest in finding out more about the veterinary profession in general. 11, 911 people signed up for the course, and of these, 8137 interacted in some way with the course and 1716 received a certificate of completion. The majority of participants (84 per cent) were female, and there was a wide age range (under 18 to over 65). Most participants were from North America or the UK. 65 per cent of those completing the entry survey were hoping or intending to work in the vet profession in the future, while 33 per cent were not. Qualitative data indicated that the course was helpful in aiding those undecided as to whether they wanted to be a veterinarian or not to decide one way or another whether they want to pursue veterinary medicine as a career. Furthermore, the course was seen as being a useful introduction to the veterinary profession even for those who had no intention of working in the field.